Validation process of Toronto Exremity Salvage Score in Italian: A quality of life measure for patients with extremity bone and soft tissue tumors. Issue 4 (19th January 2020) - Rossi, Laura; Boffano, Michele; Comandone, Alessandro; Ferro, Andrea; Grignani, Giovanni; Linari, Alessandra; Pellegrino, Pietro; Piana, Raimondo; Ratto, Nicola; Davis, Aileen M.
Abstract: Background and Objectives: Limb salvage surgery remains the standard treatment in bone and soft tissue tumors. Toronto Extremity Salvage Score (TESS) is the most used quality of life measure. Our objective was to perform cross‐cultural adaptation and validation in Italian, testing test‐retest reliability, construct validity, and responsiveness. Methods: We interviewed patients already treated for content validity. A total of 124 patients completed TESS and other questionnaires presurgery, at 3 months, 3 months + 2 weeks, and 6 months follow‐up. We calculated intraclass correlation coefficients (ICCs) for reliability, associations with Pearson's r, and change over time with paired T tests. Results: A new item regarding touch‐screen devices was added to the upper extremity (UE) questionnaire. ICC resulted of 0.99 for lower extremity (LE) and 0.98 for UE patients, Pearson's r between TESS and Musculoskeletal Tumor Society was .66 and .64, EuroQol‐5D‐5L r was .62 and .61, and r between TESS and short form‐36 physical function subscale was .76 and .71 for LE and UE groups, respectively. Paired T test results were statistically significant to detect change over time (0.03, 0.04, and 0.04 for LE groups and 0.03, 0.01, and 0.04 for UE groups). Conclusion: The Italian version of TESS can be used for the bone and soft tissue sarcoma population in clinical trials in Italy and with Italian speaking patients abroad to ensure patients' perspectives for efficacy and efficiency of treatments.